Medical Jousting - Sharma, Anup (Journal of Nepalgunj Medical College, 2024)
The definition of jousting according to the “Oxford Dictionary” is a sporting contest in which two opponents on a horseback, typically knights, fight with lances. Medical jousting is when a medical professional makes derogatory comments about another medical professional’s work or treatment, either intentionally or unintentionally. It can be verbal, written or conveyed through body language. It is usually done due to jealousy against a fellow colleague. Jealousy can be interms of knowledge, number of patients that is seen by a fellow colleague and in today’s time especially in surgical practice, whether the procedure done is minimally invasive or open surgical. The common ways of medical jousting is by passing comments like did the doctor examined the patient thoroughly, why this treatment was done why not other, if you have come to me first, I would have done like this, who gave you this scar, I would have avoided and so on. Medical jousting has both ethical and legal implications. It leads to reduction in the trust towards the medical professional and stimulate the patient to file a case on a ground of malpractice or the patient is forced to do “Doctors Shopping” and end up in confusion and in worst situation it can provoke physical attack on a medical professional. Difference in opinion about the treatment of many diseases between two doctors or a critical review of an article by a reviewer is well accepted. There are many controversies in the diagnostic and therapeutic procedures of diseases around the world. To prevent medical jousting, medical professionals should have no feeling of jealousy or opposition among the colleagues. If any incompetency is found in the treatment by the primary physician, the second should better not mention it to the patient or his/her relatives and if it is very important to mention it can be discussed by himself personally.